A STEM Approach Concerning Educational Robotics in Interdisciplinary Teacher Training - Rodrigues, Ana Luiza; Batista, Filipe A.; Aragão, Isabelle Rodrigues; Santos, Larissa P. C.; Oliveira, Marcus J. A. De; Koike, Carla M. C. C.; Viana, Dianne M.; Yudi, Jones (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
The growing incentive to atract students to STEM (Science, Technology, Engineering, Math) areas, has lead to several studies reported in the literature about teaching methodologies and techniques for STEM, with different approaches, whether more classical (active teacher, passive student) or more modern (guiding teacher, active student). In this work, instead of focusing on the student learning process, we deal with training for teachers. Volunteer teachers from public high schools participated in formative training, complementing their training from specific subjects, focusing on three workshops: mechanical modelling and 3D printing; algorithms and programming concepts; Arduino and mechatronics. Each workshop was prepared and supervised by university professors, and then carried by engineering and education undergraduate students as instructors. The workshops used an educational robot project as a guide and incentive. Diverse pedagogic elements were integrated in order to show educational possibilities. This paper presents the steps related to the workshops’ conception, planning and implementation, focusing on how the didactic elements were defined and ways to approach the contents. The results show the performance and quality analysis and proposals for improvements and new solutions.